1999
DOI: 10.1142/s0217984999000816
|View full text |Cite
|
Sign up to set email alerts
|

THE OPTICAL AND EPR SPECTRA OF THE HYDROGEN ANNEALED KTiOPO4 CRYSTALS

Abstract: In this work, the results of the hydrogen treatment and following that, the annealing in air of flux-grown KTiOPO 4 (KTP) crystals are represented. We have tried to correlate our optical and EPR results. The main conclusion is that the Ti 3+ A, B, C, D centers are not associated with optical absorption in the visible light region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…KTP crystals were extensively studied by various methods, 22,23 including Electron Paramagnetic Resonance (EPR) of impurities [24][25][26][27][28][29][30][31] and radiation defects. 32 one Pt 3þ center, Pt(A), and two Pt þ centers, Pt(B) and Pt(C), were described in details.…”
mentioning
confidence: 99%
“…KTP crystals were extensively studied by various methods, 22,23 including Electron Paramagnetic Resonance (EPR) of impurities [24][25][26][27][28][29][30][31] and radiation defects. 32 one Pt 3þ center, Pt(A), and two Pt þ centers, Pt(B) and Pt(C), were described in details.…”
mentioning
confidence: 99%
“…KTP crystals were extensively studied by various methods, 9,[19][20][21] including Electron Paramagnetic Resonance (EPR) of impurities [22][23][24][25][26][27][28][29][30][31] and radiation defects. 32 found that EPR signal depends on kind of irradiation (light, x-and c-rays), as well as on growth technique.…”
mentioning
confidence: 99%